2009
DOI: 10.1097/01.ogx.0000359275.06725.09
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Age-Specific Risk of Nonchromosomal Anomalies

Abstract: Objectives To determine the excess risk of non-chromosomal congenital anomaly (NCA) among teenage mothers and older mothers.Design and setting Population-based prevalence study using data from EUROCAT congenital anomaly registers in 23 regions of Europe in 15 countries, covering a total of 1.75 million births from 2000 to 2004.Participants A total of 38 958 cases of NCA that were live births, fetal deaths with gestational age ‡20 weeks or terminations of pregnancy following prenatal diagnosis of a congenital a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Our study also observed the association of lower maternal age and increased risk of septo-optic dysplasia, which has been noted in several studies (Elster andMcAnarney 1979, Lippe et al 1979 Murray et al 2005, Khaper et al 2017. There are only a few congenital anomalies that are associated with younger maternal age, with gastroschisis having the strongest association (Loane et al 2009). As we have shown for septo-optic dysplasia, the prevalence of gastroschisis is also higher in the UK compared to continental Europe (Loane et al 2007) and the aetiology is considered to be a result of a vascular disruption (van Gelder et al 2010).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our study also observed the association of lower maternal age and increased risk of septo-optic dysplasia, which has been noted in several studies (Elster andMcAnarney 1979, Lippe et al 1979 Murray et al 2005, Khaper et al 2017. There are only a few congenital anomalies that are associated with younger maternal age, with gastroschisis having the strongest association (Loane et al 2009). As we have shown for septo-optic dysplasia, the prevalence of gastroschisis is also higher in the UK compared to continental Europe (Loane et al 2007) and the aetiology is considered to be a result of a vascular disruption (van Gelder et al 2010).…”
Section: Discussionsupporting
confidence: 88%
“…This sensitively analysis was carried out as, from previous studies, it was expected that fetuses of younger mothers would have a higher risk of septooptic dysplasia (Elster and McAnarney 1979, Lippe 1979, Murray et al 2005, Atapattu et al 2012. This is unusual and the other main anomaly in which this age-related risk is seen is gastroschisis (Loane et al 2009). Gastroschisis has a high prevalence in younger mothers in the UK compared to the rest of Europe (Loane et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of chromosomal anomalies, most CAs are not strongly associated with maternal age [37]. However, gastroschisis, an abdominal wall defect, is associated with young maternal age [38] and it was necessary to adjust the gastroschisis-medication exposure association for maternal age.…”
Section: Signal Validationmentioning
confidence: 99%
“…Furthermore, information on the variation in prevalence of specific CHD phenotypes with maternal age is limited by the inconsistency in the type of CHDs examined and the mixed results observed across studies. For example, while one investigator [Pradat et al, 2003] found a significant association between advanced maternal age and tetralogy of Fallot and atrioventricular septal defects (AVSDs), other investigators did not [Baird et al, 1991;O'Malley et al, 1996;Loane et al, 2009]. Furthermore, very few studies have been populationbased and have accounted for possible effect modifiers such as low birth weight (LBW), preterm delivery, maternal race, and infant sex.…”
Section: Introductionmentioning
confidence: 99%